Frozen a taken novel - Bowman, Erin (HarperTeen / HarperCollins, 2014)
"Gray Weathersby and a small team of rebels set off on a frozen, icy journey in search of allies to help them take down the cruel Franconian Order--but they quickly learn that no ally or enemy is truly what they seem"--Provided by publisher